The Long-Term Effect of Biochar on Soil Microbial Abundance, Activity and Community Structure Is Overwritten by Land Management - Hardy, Brieuc; Sleutel, Steven; Dufey, Joseph E.; Cornelis, Jean-Thomas (Frontiers in Environmental Science, 2019)
Soil amendment with biochar can modify soil microbial abundance, activity and community structure. Nevertheless, the long-term evolution of these effects is unknown and of critical importance because biochar persists in soil for centuries. We selected nine charcoal kiln sites (CKS) from forest (4 sites) and cropland (5 sites) and determined microbial properties of their topsoil, largely enriched with charcoal for > 150 years. Adjacent soils were used as references unaffected by charcoal production. Soils were incubated in controlled conditions and emissions of CO2 were measured during 138 days. At day 68, an aliquot was sampled from each soil to determine microbial abundance and community structure by phospholipid fatty acid (PLFA) analysis. Before the extraction, one standard PLFA (C21:0 PC) was added to soil to test the influence of charcoal on PLFAs recovery. The content of uncharred SOC and pH explained a main part of the variance of soil CO2 emissions, which supports the view that charcoal had a limited effect on soil respiration. The recovery of C21:0 PC was increased in presence of aged charcoal, which contrasts with the decreased recovery recorded shortly after biochar application. This underlines that properties of charcoal evolve dramatically over time, and that a long-term vision is critical in the perspective of amending soils with biochar. Land-use had an overriding control on microbial community structure, surpassing the effect of a vast amount of charcoal present in the soil. In forest, 10 PLFAs from gram positive and general bacteria were significantly different between CKS and adjacent reference soils, whereas in cropland only four PLFAs from fungi, gram negative bacteria and actinomycetes were significantly affected. These results suggest that the long-term effect of charcoal on soil microbiota is overwritten by management practices. Biochar properties must therefore be regarded altogether with soil conditions to correctly design a successful soil amendment with biochar. Additionally, the absence of relationship between individual PLFAs and charcoal-C supports the idea that the long-term effect of charcoal is related to a modification of soil ecological niche (e.g. nutrient availability, pH) rather than to an alteration of the source of organic C available to biota.